Advancing Rural Development: Sustainable Tourism Practices in the Evolution of Cibeusi Tourism Village, Subang Regency, Indonesia - Bahreisy, Afghani Mahmuda; Maturbongs, Bagas Dwie Abrinzar Prajan; Ridwan, Okky Rizal; Mas Multazam (International Journal of Sustainable Competitiveness on Tourism, 2025)
A tourist village is an area with potential rural tourism attractions and distinctive traditions owned by a village. This research is located in Cibeusi Tourism Village in Subang Regency, West Java. Tourism villages are developing as travel trends change from mass tourism to alternative tourism. Good management of tourist villages is needed for community benefits, with two approaches: community-based tourism and sustainable tourism. The research aims to see how the focus of sustainable tourism-based tourism village development conducted by Cibeusi Tourism Village. The method used is descriptive qualitative with semi-structured interview techniques, field observation, and documentation. The results showed that the Cibeusi Village community was active in the design, management, and evaluation of tourism activities, which also helped the economy through the provision of employment. Tourism village development also pays attention to environmental arrangements and conservation efforts.